2014
DOI: 10.5588/ijtld.13.0198
|View full text |Cite
|
Sign up to set email alerts
|

Estimating tuberculosis burden and case detection in Pakistan

Abstract: The study estimated that the proportion of cases notified to the NTP was low, with actual incidence rates being higher than official estimates. TB surveillance should be strengthened to reduce under-reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 77 publications
5
27
0
Order By: Relevance
“…The incidence was 231 per 100,000 population in 2012 that only 64% of new cases were determined and unknown number of patients were missed out. The incidence of tuberculosis in 2013 was 275 in 100,000 population [25,26]. h) Iraq Iraq is among seven tuberculosis contaminated in the eastern Mediterranean countries and occupied rank 108 4 Zahedan J Res Med Sci.…”
Section: Tuberculosis In Neighboring Countries Of Iranmentioning
confidence: 99%
“…The incidence was 231 per 100,000 population in 2012 that only 64% of new cases were determined and unknown number of patients were missed out. The incidence of tuberculosis in 2013 was 275 in 100,000 population [25,26]. h) Iraq Iraq is among seven tuberculosis contaminated in the eastern Mediterranean countries and occupied rank 108 4 Zahedan J Res Med Sci.…”
Section: Tuberculosis In Neighboring Countries Of Iranmentioning
confidence: 99%
“…1 Furthermore, a capture-recapture study showed an underestimation of TB incidence in Pakistan compared to official estimates, with an actual case detection rate of only 32%. 2 All this implies that we are currently 'missing' many patients with TB. This is a global problem; the latest WHO report states that worldwide there are 4.3 million TB cases who are 'missing', i.e., undiagnosed, untreated or treated in the private sector but not reported.…”
mentioning
confidence: 99%
“…Case detection is part of the diagnostic process from the identification of the respiratory symptom to laboratory confirmation. The reporting is an action subsequent to the diagnostic confirmation that allows an accompaniment of the disease, aiming at the dissemination of the information to the management organs in order to assist in the decision making for the control of the disease (1,3) . Although several researchers emphasize the importance of detecting and notifying TB cases for disease control (1,(4)(5)(6) , in Mozambique these actions fall far short of the numbers estimated by the World Health Organization (WHO) (4) .…”
mentioning
confidence: 99%